How Does Complement Affect Hematological Malignancies: From Basic Mechanisms to Clinical Application - Luo, Shanshan; Wang, Moran; Wang, Huafang; Hu, Desheng; Zipfel, Peter F.; Hu, Yu (Frontiers in Immunology, 2020)
Complement, as a central immune surveillance system, can be activated within seconds upon stimulation, thereby displaying multiple immune effector functions. However, in pathologic scenarios (like in tumor progression), activated complement can both display protective effects to control tumor development and passively promotes the tumor growth. Clinical investigations show that patients with several hematological malignancies often display abnormal level of specific complement components, which in turn modulates complement activation or deregulated cascade. In the past decades, complement-dependent cytotoxicity and complement-dependent cell-mediated phagocytosis were fully approved to display vital roles in monoclonal antibody-based immunotherapies, especially in therapies against hematological malignancies. However, tumor-mediated complement evasion can present a big challenge for such a therapy. This review aims to provide an integrative overview on the roles of the complement in tumor promotion, highlights complement mediated effects on antibody-based immunotherapy against distinct hematological tumors, hopefully to provide a theoretical basis for development of complement-based cancer targeted therapies.